First Report of Corky Roots of Lettuce (Lactuca sativa) Associated with Paratylenchus projectus - Giyoon Kwon (Research in Plant Disease, 2019)
Severe damage on a greenhouse grown lettuce (Lactuca sativa L.) associated with Paratylenchus projectus is described for the first time. There were no marketable lettuce in entire greenhouse after three months of planting. Lettuce roots system appeared corky and most of feeder rootlets disappeared. Population densities of P. projectus were ranged from 320–11,600 nematodes per 100 cm3 of soil. In an inoculation test in a greenhouse, P. projectus is proved as a causal agent of lettuce damage.